An enhanced anonymity resilience security protocol for vehicular ad-hoc network with Scyther simulation. (March 2020) - Amin, Ruhul; Lohani, Paras; Ekka, McLican; Chourasia, Sunay; Vollala, Satyanarayana
Abstract: Vehicular Ad-Hoc Network (VANET) refers to the wireless interconnection of vehicles for exchanging useful information among them. The transmitted information provides insight into safety and comfort in driving. It is also used in the analysis of traffic, road safety measures, vehicle performance data, and multimedia data transfer between vehicles using uninterrupted Internet connectivity. Adversaries can create several interruptions in the system after extracting sensitive information. Hence, a robust security protocol is essential to establish secure communication. In this article, we investigate the Bidi et al.'s protocol and find that the protocol has several important security flaws. We then propose a robust protocol that guarantees high-level security protection on the existing security attacks and additionally, protects all related possible attacks. Furthermore, our simulation using Scyther confirms that all the private information is protected during establishing a common key. All the performance factors of the protocol are also superior in comparison with existing works.